(untitled) (International Journal of Smart Agriculture, 2023)
Background: The Libyan economy depends on oil, which contributes more than 45% of GDP and earn the country more than 90% of its foreign exchange. While Agriculture activities producing only 3- 5% of the GDP and employs around 6% of the workforce. The low agricultural productivity of most of the crops cultivated together with rising demand for food has turned Libya into a net food importer. Objectives: an advanced development of productivity of food crops especially cereals, olives and date palm needs a very trusted data that enhance the efforts of agriculture development. So the present study aims to analyze the UN data. Data collection: data were collected from FAO and another UN reports. Results: the agriculture sector shared only (0.7 – 1.1%) of the total Libyan GDP during the period of 2000 - 2018. The highest ratio recoded in 2000 and 2005 gaining 1004.4 and 1268.5 USD million dollars. the crop land area ranged between (2,050,000 – 2,150,000 ha) during the period 2000 – 2018. The per capita crop land ranged (0.31 0.4 ha). The percentage of area equipped for irrigation in land area ranged (2.6 – 3.0%). The area of agriculture land ranged (15,350,000 – 15,450,000 ha) during the same period. While the area of forest land recorded (217,000 ha) during the same period. the total percentage of workforce in agriculture sector ranged between (18.4 – 24%). The percentage of women share in agriculture employment recorded (35.9 – 40.8 %) of the total agriculture workforce during the same period. the percentage of gross fixed capital formation (agriculture, forestry and fishing) as a share of value added recorded (6.9 -15.7%). the pesticide use per cropland area recorded (0.51 – 1.34 kg per ha) during the period 2000 - 2018. the total consumption of chemical fertilizers ranged (8.3 -25.6) (kg per ha) during the same period. fruits recorded the highest amount of the total agriculture production (696,000 tons) followed by vegetables (682,000 tons). the total agriculture production recorded (2,210,000 tons) in 2018. the total food exports, 2018 recorded (43 USD millions), fish recorded the highest value (36 USD millions) followed by fruits and vegetables (6 USD millions). the total food imports recorded (3167 USD millions), cereals recorded the highest value (975 USD millions) followed by dairy (420 USD millions) while, beverage was the lowest (81USD millions). Wheat recorded the highest amount among cereal crop imports (1461.8 thousand tons) followed by maize (784.3 thousand tons) and rice (101.2 thousand tons). Moreover. water stress percentage ranged (615.4 – 817.1%) during the period 2000 – 2018